Identifikasi Koleksi Jamur dari Cangkang dan Pasir Sarang Telur Penyu Lekang (Lepidochelys olivacea L.) di Penangkaran Pariaman - Selfia Anwar; Fuji Astuti Febria; Nasril Nasir (Jurnal Biologi Universitas Andalas, 2014)
The district of Pariaman has a conservation site for sea turtles, including olive ridley (Lepidochelys olivacea L.). Several reports have stated that fungus infect egg of the turtles and caused the failure of hatching. However, there is no study on this site yet. The aim of this study was to identify fungus on turtle's egg, hatched and inhatched nest sand. Collection and identification were conducted from December 2012 until June 2013 in turtles’ breeding in Pariaman and Microbiology Laboratory of Biology Department of Mathematic and Natural Sience, Andalas University. Result showed that Fusarium sp. 1, Fusarium sp. 2, Fusarium sp. 3, Fusarium sp. 4, Fusarium sp. 5, Fusarium sp. 6, Fusarium sp. 7 dominated among identified fungus, other were Aspergillus sp. 1 and Trichoderma sp. 1 and than there was no fungus found on hatched egg. Keywords: Identification, Fungus, Egg shell, Nest sand, Lepidochelys olivacea L.